FIVE GLASS BONES OF STRATEGIC MANAGEMENT THEORY - Bacanu Bogdan (Annals of the University of Oradea: Economic Science, 2014)
The present work takes into account the consistency of five reference points considered as highly significant for the current strategic management: the strategy, the competitive advantage, the five forces model, the VRIO framework and the generic strategies. They have been selected by taking into account both the frequency of their use in the textbooks, and also the consequences they have generated in the field theory and research. The study starts by considering the main reference points which assume the role of defining the selected concepts, in order to develop an analysis by highlighting their debatable features. The relation between concepts and virtual implications of the current stage in their development represents an implicit aim of this work. The methodological framework approached considers, as preliminary elements, the works referring the concepts in question and the significant milestones related to their approval. The next step is to take into account some critical references, assuming positions that contradict those promoted by the previous works. They enjoy a fairly limited popularity, which makes them more interesting for the development of an approach which counterbalances the standardized textbooks, characterized by a lush amount of bibliography that complies with the official trend. The methodology used is of qualitative type. At the first stage, an analysis of concept definitions and proximate elements is developed. Afterwards the results of certain empirical studies validating the concepts discussed are taken into account. Their results relate to the critical positions assumed by studies which raise an amount of relevant points of discussion. A logical filter has been used in order to mitigate the groupthink oriented effect caused by the appraisal of concepts in the American textbooks. In an absolutely predictable manner, the analysis results are able to temper the academic conformism involved in the dissemination of strategic management. One can infer there is enough evidence available for questioning the reliability of the whole field structure involved in the economic sector. An extreme frailty can be distinguished for a great amount of concepts and connected elements, a frailty able to generate insurmountable dilemmas for the practical use. The discussion dealing with the weak points of the researched concepts questions the reliability of the results acquired by empirical research, considered as relevant by the supporters of the current situation in the theory development. In practice, the problem of utilizing the tools derived from the studied concepts will be addressed, due to the fact that the results will be influenced by the problems identified as results of the present study. The topic selection relates this study to the category of works attempting at a more realistic approach of the “made in USA” theory. The author has selected the key concepts to be analyzed, identifying the most sensitive points involved in the theoretic elements network, developed on the basis of these concepts.